The Emergence of Ornamental Horticulture and Garden Art - Q, Ruziboyeva D.; B, Xo`jayorova O.; B., Kadirova SH. (Researchparks Publishing, 2023)
The choice of landscape design style It is necessary to take into account its configuration, size and environment. Moreover, it is necessary to take into account the architectural style of the house itself and the structures on the territory. It is very important that everything looks harmonious.